Distributed Authentication of Power Grid Safety and Stability Control Terminals Based on DHT and Blockchain - Yening LAI; Ke FENG; Tongwei YU; Wang WANG; Guanjun TANG (Zhongguo dianli)
The power grid safety and stability control system has limited terminal resources and high requirement for real time response, and existing authentication schemes can hardly satisfy the requirements of the system for safety, real-time ability and storage efficiency. By combining the distributed Hash table (DHT) technology with the blockchain technology, a blockchain distributed storage optimization method is firstly proposed based on DHT of Skip Graph structure. And then a distributed authentication scheme of power grid safety and stability control terminals is designed based on DHT and blockchain technology, and the process and key algorithms for terminal registration, network access and authentication are given. The safety and spatial-temporal complexity of the proposed scheme are analyzed. The authentication scheme is systematically implemented, and experiments are performed on its average authentication latency and average terminal storage cost, which has verified the feasibility of the proposed scheme and its advantages in spatial-temporal efficiency. The proposed scheme improves the communication safety between terminals of the power grid safety and stability control system without affecting the communication efficiency, thus ensuring the safe and stable operation of power grid.